Is God a Rule-consequentialist?: Bayesian and total probability arguments - Hunt, William (European journal for philosophy of religion, 2022)
Prima facie, rule-consequentialism as a moral theory would correlate with the concerns of an omnibenevolent being should one exist. Indeed, such a being would be divine, and under the lenses of the three Abrahamic religions, would inter alia, also be omnipotent and omniscient. In this paper, I consider the attitude of such a being to rule-consequentialism in human society. I argue, from a probabilistic perspective, that the evidence of Abrahamic scripture confirms, to a degree, that God would judge rule-consequentialism to be a sound moral theory in different societies. I also consider a similar argument from a secular perspective.